A modified Herschel–Bulkley model for rheological properties with temperature response characteristics of poly-sulfonated drilling fluid. Issue 12 (17th June 2020) - Huang, Yuming; Zheng, Wenlong; Zhang, Dingyu; Xi, Yawen
ABSTRACT: In the deep oil and gas drilling operations, estimation and prediction of the rheological properties for a drilling fluid are of crucial importance for precisely hydraulic calculating, cuttings carrying and wellbore stability controlling. Unfortunately, the existing well-known rheological models, such as Bingham Plastic, Power Law, Casson, and Herschel–Bulkley models neglect the effect of temperature on the apparent viscosity of water-based drilling fluid. In this paper, the rheological behavior of the poly-sulfonated drilling fluid applied to the Well SK-2 in Songliao basin, China, within a temperature range of 60–240°C, were experimentally determined using a FANN 50SL rheometer. Results showed that the apparent viscosity decreases with the increase of temperature, especially at the low shear rates. In the whole shear rate range, the rheology curve was divided into two parts. At low shear rates (<170.3 s −1 ), the Herschel Bulkley model fitted well with the measured data, while at higher shear rates (>170.3 s −1 ), the Bingham Plastic model got higher precision. Based on the viscosity equation recommended by the American Petroleum Institute, the temperature factor was introduced to modify the Herschel-Bulkley equation, and the apparent viscosity can be successfully predicted compared with the other commonly used rheological models.